1990
DOI: 10.1111/j.1365-2044.1990.tb14697.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressor responses to tracbeal intubation after sublingual captopril A pilot study

Abstract: SummaryThe effect of sublingual captopril on the pressor response to intubation was studied in 40 patients. Captopril was used in one of two doses (12.5 mg and 25 mg) 25 minutes before tracheal intubation. Both doses were associated with a significant reduction in the pressor response to intubation (p < 0.05) compared to placebo, but no significant difference existed between the two doses. Neither dose controlled changes in heart rate at intubation. Untoward hypotension occurred in the treatment groups. Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
5

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
0
4
0
5
Order By: Relevance
“…Nichtinvasiver Blutdruck und Herzfrequenz wurden ab 5 min vor Beginn der Einleitung bis 10 min nach Intubation alle 60 s gemessen. In diesem Zeitfenster sind die ausgeprägtesten Kreislaufreaktionen zu erwarten [4,14]. Bei der Narkoseausleitung wurden diese Messungen ab 2 min vor bis 5 min nach Extubation dokumentiert.…”
Section: Studieunclassified
See 3 more Smart Citations
“…Nichtinvasiver Blutdruck und Herzfrequenz wurden ab 5 min vor Beginn der Einleitung bis 10 min nach Intubation alle 60 s gemessen. In diesem Zeitfenster sind die ausgeprägtesten Kreislaufreaktionen zu erwarten [4,14]. Bei der Narkoseausleitung wurden diese Messungen ab 2 min vor bis 5 min nach Extubation dokumentiert.…”
Section: Studieunclassified
“…In der Diskussion zum perioperativen Absetzen vs. der Weitergabe einer ACE-Hemmer-Medikation wird fast ausschließlich auf Studien verwiesen, bei denen genau diese Fragestellung gar nicht untersucht wurde, sondern ACE-Hemmer-behandelte Patienten mit Kontrollgruppen ohne ACE-Hemmer verglichen [4,6,11,13,19] oder die Wirkung einer präoperativen ACE-Hemmer-Gabe [12,14,22] …”
Section: Diskussionunclassified
See 2 more Smart Citations
“…McCarthy and coworkers studied the pressor response to tracheal intubation in 40 patients following sublingual captopril or placebo [88]. They found that treatment was successful at preventing excessive increases in arterial blood pressure during laryngoscopy after the administration of thiopentone, vecuronium, nitrous oxide and isoflurane.…”
Section: Ace Inhibitors In Surgery and Anaesthesiamentioning
confidence: 99%